Effect of Hesperidin on Barrier Function and Reactive Oxygen Species Production in an Oral Epithelial Cell Model, and on Secretion of Macrophage-Derived Inflammatory Mediators during Porphyromonas gingivalis Infection - Maquera-Huacho, Patricia Milagros [UNESP]; Spolidorio, Denise Palomari [UNESP]; Manthey, John; Grenier, Daniel (MDPI, 2023)
Porphyromonas gingivalis is a periodontopathogenic bacterium that can adhere to and colonize periodontal tissues, leading to an inflammatory process, and, consequently, tissue destruction. New therapies using flavonoids, such as hesperidin, are being studied, and their promising properties have been highlighted. The aim of this study was to evaluate the effect of hesperidin on the epithelial barrier function, reactive oxygen species (ROS) production, and on the inflammatory response caused by P. gingivalis in in vitro models. The integrity of the epithelial tight junctions challenged by P. gingivalis was determined by monitoring the transepithelial electrical resistance (TER). P. gingivalis adherence to a gingival keratinocyte monolayer and a basement membrane model were evaluated by a fluorescence assay. A fluorometric assay was used to determine the ROS production in gingival keratinocytes. The level of pro-inflammatory cytokines and matrix metalloproteinases (MMPs) secretion was evaluated by ELISA; to assess NF-κB activation, the U937-3xjB-LUC monocyte cell line transfected with a luciferase reporter gene was used. Hesperidin protected against gingival epithelial barrier dysfunction caused by P. gingivalis and reduced the adherence of P. gingivalis to the basement membrane model. Hesperidin dose-dependently inhibited P. gingivalis-mediated ROS production by oral epithelial cells as well as the secretion of IL-1β, TNF-α, IL-8, MMP-2, and MMP-9 by macrophages challenged with P. gingivalis. Additionally, it was able to attenuate NF-κB activation in macrophages stimulated with P. gingivalis. These findings suggest that hesperidin has a protective effect on the epithelial barrier function, in addition to reducing ROS production and attenuating the inflammatory response associated with periodontal disease.
Keywords: hesperidin; inflammation; keratinocyte; macrophage; oxidative stress; Porphyromonas gingivalis